Non-invasive Amino Acid Profiling of Embryo Culture Medium Using HPLC Correlates With Embryo Implantation Potential in Women Undergoing in vitro Fertilization - Huo, Peng; Zhu, Yunshan; Liang, Chengqin; Yao, Jun; Le, Jianghua; Qin, Linyuan; Lei, Xiaocan; Zhang, Shun (Frontiers in Physiology, 2020)
This study aimed to determine the correlation between amino acid profiling of day 3 embryo culture medium and embryo implantation potential in women undergoing in vitro fertilization (IVF). The data of 98 patients received IVF treatment in our hospital from December 2015 to February 2017 were retrospectively analyzed. The 98 patients were into pregnant group (gemellary pregnancy), non-pregnant group (non-pregnancy) and blank control group. The amino acids from day 3 embryo culture medium and blank control medium were collected and were analyzed using high performance liquid chromatography (HPLC). The HPLC results showed that amino acids including aspartate (ASP), serine (SER), glycine (GLY), histidine (HIS), taurine (TAU), arginine (ARG), threonine (THR), alanine (ALA) and proline (PRO) were detected in the day3 embryo culture medium and blank control medium. There are significant differences between pregnant group and non-pregnant group in H-SER, S-ASP, S-SER, S-HIS and S-ALA. The discrimination analysis according to the peak height and peak area of amino acids revealed that the prediction rate of the pregnant group, non-pregnant group and blank control group were 82.7%, 95.7% and 100%. Further by using the principal component analysis, we found that the prediction rate in these three groups were 90.4%, 91.3% and 100%. Our data may suggest that using amino acid concentrations for PCA and discriminant analysis has high accuracy in predicting the relationship between amino acid fingerprint and embryo implantation potential.